Trait Impulsivity Is Independent of Mild Cognitive Impairment in a Parkinson’s Disease Cohort - Ashani Jeyadevan; Megan C. Bakeberg; Michelle Byrnes; Jade Kenna; Soumya Ghosh; Rick Stell; Sue Walters; Tess Evans; Sarah McGregor; Malcolm Horne; Frank L. Mastaglia; Ryan S. Anderton (Parkinson's Disease)
Introduction. Patients with Parkinson’s disease (PD) commonly experience cognitive deficits and some also develop impulse control disorders (ICDs); however, the relationship between impulsivity and cognitive dysfunction remains unclear. This study investigated whether trait impulsivity associates with mild cognitive impairment (MCI), or is altered in a PD patient cohort with MCI. Methods. A total of 302 patients with idiopathic PD were recruited sequentially from three Australian Movement Disorder clinics. Based on cognitive scores, participants were divided into two groups, one defined as having mild cognitive impairment (PD-MCI; n = 113) and the other with normal cognitive function (PD-C; n = 189). Trait impulsivity was evaluated using the Barrett Impulsiveness Scale 11 (BIS-11). Total impulsivity scores, as well as subscale scores, were compared between PD-C and PD-MCI groups. Results. The PD-MCI cohort had significantly lower scores in all cognitive domains, and mirrored expected clinical differences in medication, motor symptoms, and disease duration, when compared to the PD-C cohort. Self-reported impulsivity was not significantly different between groups, nor was there a difference within first-order subscale scores: attention p=0.137, cognitive instability p=0.787, self-control p=0.503, cognitive complexity p=0.157, motor impulsivity p=0.559, or perseverance p=0.734 between the PD-MCI and PD-C groups. Conclusions. These findings suggest that impulsive traits and behaviors are independent of changes in cognitive state and are not altered in PD patients with mild cognitive impairment.